FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN UNQUALIFIED OPINION WITH MODIFIED PARAGRAPH GOING CONCERN - YOLANDA WINATA; AAN MARLINAH (Media Bisnis, 2015)
The purpose of the research is to find out the influence of financial condition, firms’s size, auditor reputation, previous year audit opinion, firm’s growth, liquidity and return on asset on assessing unqualified opinion with paragraph going concern to non financial companies which is listed in Indonesia Stock Exchange during 2008 till 2011. These samples included 40 non financial companies during 4 year observation periods so that this research got 160 of research samples. The sampling technique used in this research was purposive sampling. Hypothetical research was analyzed using logistic regression. The result of the research show that financial condition, auditor reputation and previous year audit opinion have influence on assessing going concern audit opinion. While, firms’s size, firm’s growth, liquidity and return on asset have not influence on assessing unqualified opinion with paragraph going concern.